1989
DOI: 10.3168/jds.s0022-0302(89)79161-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Reproductive Tissue for Detection of Estrus in Dairy Cows

Abstract: The pattern of temporal measurements of electrical conductivity obtained from electrodes that had been surgically implanted in the mucosa of the vagina or in the submucosa of the vulva in each of five dairy cows was evaluated for changes associated with the occurrence of estrus. Tissue conductivity was monitored at 6-h intervals during and around estrus by hard-ware devices operating at either 16 or 100 kHz. Blood samples were taken at time of conductivity measurement for progesterone determination and at 2-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…On the other hand, the present study showed that the estrous signs in the vulva and vagina were observed more clearly in all lactating and non-lactating cows compared with those related to behavior. Although there are no reports examining the appearance of vaginal estrous signs and their duration in cows by using vaginoscopy, vaginal temperature [14] and electrical conductivity of the vaginal mucus [36] have been reported to be closely associated with the onset of estrus and time of ovulation. At estrus, high levels of estrogens increase blood flow in the reproductive tract, causing increased vaginal hydration and mucous discharge [4].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the present study showed that the estrous signs in the vulva and vagina were observed more clearly in all lactating and non-lactating cows compared with those related to behavior. Although there are no reports examining the appearance of vaginal estrous signs and their duration in cows by using vaginoscopy, vaginal temperature [14] and electrical conductivity of the vaginal mucus [36] have been reported to be closely associated with the onset of estrus and time of ovulation. At estrus, high levels of estrogens increase blood flow in the reproductive tract, causing increased vaginal hydration and mucous discharge [4].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta and Purohit (2001) reported that AI at a low VEI distinctly improved the conception rate in buffaloes. Data obtained in cattle with electrodes implanted in the vaginal submucosa, 15 cm from the vulva, indicate that changes in vaginal impedance have a closer relationship to the timing of ovulation than to the timing of estrus (Smith et al, 1989). During this experiment, typical changes in VEI of individual crossbred cows with a postpartum period of 40-96 days were observed daily up to 42 days to record the minimum level of resistance and the moment when a distinct rise in resistance occurred.…”
Section: Discussionmentioning
confidence: 99%
“…High density industrial farming can also be potentially dangerous for humans e.g. due to the increased use of drugs and the consequent rise of antibiotics resistant bacteria (Pu et al, 2009;Smith et al, 2005). From a purely economic perspective, excessive use of pesticides and pre-emptive use of drugs frequently make sense since one of the main costs associated with farming is that of labour.…”
Section: Motivationmentioning
confidence: 99%
“…This excludes the circadian variations from being a factor. According to established theory, (Wrenn et al, 1958;Smith et al, 1989) estrus is concomitant with a local temperature maximum following a global minimum, and a global maximum in conductivity. Both the temperature and conductivity data obtained with this probe are in full qualitative agreement with the expected behaviour.…”
Section: Accelerationmentioning
confidence: 99%
See 1 more Smart Citation